A dynamic panel data approach of corporate tax avoidance and debt financing in Nigeria - Armaya'u Alhaji Sani; Isah Umar Kibiya; Mujeeb Saif Mohsen Al-Absy; Muhammad Liman Muhammad; Hussaini Bala; Ghousia Khatoon; Sani Damamisau Mohammed; Sunusi Garba (Cogent Business & Management, 2024)
This study examines the influence of corporate tax avoidance on the debt financing of listed conglomerate firms in Nigeria. The study utilized documentary data collected from the annual reports and accounts of the sampled companies from 2010 to 2021. The data were analyzed using the Generalized Method of Moments (GMM). The results of the main analysis indicate that CETR and BTD have a negative and strong association with debt policy, proxied by debt to equity and debt to total assets. These findings imply that tax avoidance is positive and therefore more likely to increase the debt capital of listed companies in Nigeria. Hence, it is recommended that the management of conglomerate firms strive to strike a balance between non-debt tax shields and a tax shield in its effort to reduce its taxable income, as the cost of conventional debt is lower.
Keywords: 650; Tax avoidance; leverage; cash effective tax rate; book to tax difference; cash flow effective tax rare